Test Procedures to Assess Somatosensory Abnormalities in Individuals with Peripheral Joint Pain: A Systematic Review of Psychometric Properties. Issue 7 (6th March 2018) - Alqarni, Abdullah Mohammad; Manlapaz, Donald; Baxter, David; Tumilty, Steve; Mani, Ramakrishnan
Abstract: Background: Test procedures that were developed to assess somatosensory abnormalities should possess optimal psychometric properties (PMPs) to be used in clinical practice. The aim of this systematic review was to evaluate the literature to assess the level of evidence for PMPs of test procedures investigated in individuals with peripheral joint pain (PJP). Methods: A comprehensive electronic literature search was conducted in 7 databases from inception to March 2016. The Quality Appraisal for Reliability Studies (QAREL) checklist and the Consensus‐based Standards for the Selection of Health Status Measurement Instruments (COSMIN) tool were used to assess risk for bias of the included studies. Level of evidence was evaluated based on the methodological quality and the quality of the measurement properties. Results: Forty‐one studies related to PJP were included. The majority of included studies were considered to be of insufficient methodological quality, and the level of evidence for PMPs varied across different test procedures. The level of evidence for PMPs varied across different test procedures in different types of PJP. Hand‐held pressure algometry is the only test procedure that showed moderate positive evidence of intrarater reliability, agreement, and responsiveness, simultaneously, when it was investigated in patients with chronic knee osteoarthritis. Conclusions: This systematic review identified that the level of evidence for PMPs varied across different testing procedures to assess somatosensory abnormalities for different PJP populations. Further research with standardized protocols is recommended to further investigate the predictive ability and responsiveness of reported test procedures in order to warrant their extended utility in clinical practice.